Investigating Stress, Psychological Well-Being, Mental Health Functioning, and Self-Regulation Capacity Among University Undergraduate Students: Is This Population Optimally Functioning? - Durand-Bush, Natalie; McNeill, Kylie; Harding, Matthew; Dobransky, Johanna (Canadian Journal of Counselling and Psychotherapy, 2015)
Two studies were conducted to assess the levels of stress, psychological well-being, mental health functioning, and self-regulation capacity of undergraduate students via an online survey. A total of 469 undergraduate students participated in Study 1 and 647 in Study 2. While the students in both studies exhibited low mental health functioning and moderate to high levels of stress, they concurrently maintained a fairly high level of well-being and moderate capacity to self-regulate. Students’ self-regulation capacity significantly predicted their levels of stress, psychological well-being, and mental health functioning. Recommendations to develop this competency through counselling and formal courses are put forth.